Physical Fitness and Motor Competence in Upper Austrian Elementary School Children-Study Protocol and Preliminary Findings of a State-Wide Fitness Testing Program - Clemens Drenowatz; Franz Hinterkörner; Klaus Greier; Klaus Greier (Frontiers Media S.A., 2021)
Motor competence and physical fitness are key components for the promotion of an active and healthy lifestyle. Poor motor competence and low physical fitness in children, therefore, are a major threat to future public health. Even though the assessment of physical fitness and motor competence per se does not enhance these entities, fitness tests can provide important information for intervention strategies. Fitness tests may also motivate children to become more active in order to increase their physical abilities. In the school-year 2016/17 the Upper Austrian government initiated the state-wide testing program "wie fit bist du" (how fit are you) in elementary schools, that examined cardiorespiratory fitness, muscular power, speed, agility, flexibility and object control skills along with the assessment of height and weight. Since the beginning of the program more than 18,000 children between 6 and 11 years of age participated in the school-based tests. The results show a significant increase in the prevalence of overweight/obesity with increasing age (p > 0.01). Overweight/obese children displayed lower motor competence and physical fitness, except for upper body strength. Further, the improvement in test performance with increasing age was less pronounced in overweight/obese children compared to their normal weight peers. In fact, distance covered during the 6-min run did not improve throughout the elementary school years in overweight/obese children. Given the importance of motor competence and physical fitness for general development and well-being, physical education should be considered a viable setting for the promotion of these entities as a majority of children can be reached independent of their socio-economic background. In order to provide adequate movement experiences that enhance motor competence and physical fitness while ensuring a motivating environment, objective information on current ability levels are required. The implementation of fitness monitoring at young ages, therefore, can be an important contributor for the promotion of an active and healthy lifestyle.